Assessment of the Frequency of Diabetes and its Complications among the Patients of District Shaheed Benazirabad Pakistan. - Bhojo Mal Tanwani1, Ali Gul Tunio2, Safdar Ali Parvez Tunio3, Shohabuddin Rind4, Riaz Hussain Khokhar5, Arslan Ahmer6, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2020)
Background: Diabetes mellitus (DM) is a syndrome of metabolic disorder and chronic hyperglycemia due to relative insulin deficiency, inefficiency or both. Diabetes Mellitus is very noxious and fatal if the proper care is not exercised. Objective: The objective of the current study is to assess the Frequency of DM Type 2 and its complications among patients of District Shaheed Benazirabad Pakistan. Methodology: The descriptive cross sectional study was carried out for eight months from June 2019 to January 2020 to find out the prevalence and triggered complications of the Diabetes Mellitus type 2. A total 300 patients were analyzed by purposive sampling technique. Data was collected by using the questionnaire instrument and their verbal consent was ensured. Chi-square test was applied to analyze the association of diabetes and its complications. Results: Results reported that there were 205 (68.33%) males and 95 (31.77%) females. It was found that prevalence of Diabetes Mellitus Type 2 was high 135 (45%) in age group of 61-70 years. Diabetic Neuropathy complication was high in 70 (23.33%) patients. It was also found that there was good glycemic control in 175 (83.33%) patients and poor in 35 (16.66%) patients. Conclusion: Most of the Patients were suffering from Diabetes Mellitus type 2 and poorly managed patients had more associated complications.